2016
DOI: 10.3329/ijns.v5i2.28613
|View full text |Cite
|
Sign up to set email alerts
|

Husbandry Practices of Dairy Farming at Chittagong Sub-urban Area

Abstract: The present study was carried out to know the present status including general information, feeding, breeding, housing, milking etc. and costs and returns of small dairy farms, to compare the productive and reproductive performance of crossbred and indigenous cows and to make recommendation for development of small scales dairy farming. With this view, the empirical data were collected by using pretested questionnaire. The study was conducted at preselected 30 dairy farms in Chittagong suburban area, and four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…A very limited number, 21% (n=6) dairy farms had sufficient own fodder land for cultivation and most of the farmers (79%, n=22) were dependent on purchased green forage. Many researches work (for example, Basset et al, 2010;Faruk et al, 2015) have shown relation to the ownership of fodder land of dairy farmers. For routine management, regularity of feeding with other routine activities such as regularity in cleaning of barn and cows at least twice a day was considered for the farm.…”
Section: Management Conditions Of the Farmsmentioning
confidence: 99%
“…A very limited number, 21% (n=6) dairy farms had sufficient own fodder land for cultivation and most of the farmers (79%, n=22) were dependent on purchased green forage. Many researches work (for example, Basset et al, 2010;Faruk et al, 2015) have shown relation to the ownership of fodder land of dairy farmers. For routine management, regularity of feeding with other routine activities such as regularity in cleaning of barn and cows at least twice a day was considered for the farm.…”
Section: Management Conditions Of the Farmsmentioning
confidence: 99%